2016
DOI: 10.1021/acschemneuro.6b00028
|View full text |Cite
|
Sign up to set email alerts
|

PKCβ Inhibitors Attenuate Amphetamine-Stimulated Dopamine Efflux

Abstract: Amphetamine abuse afflicts over 13 million people, and there is currently no universally accepted treatment for amphetamine addiction. Amphetamine serves as a substrate for the dopamine transporter and reverses the transporter to cause an increase in extracellular dopamine. Activation of the beta subunit of protein kinase C (PKCβ) enhances extracellular dopamine in the presence of amphetamine by facilitating the reverse transport of dopamine and internalizing the D2 autoreceptor. We previously demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…Consistent with this idea, PKCb knockout mice demonstrate reduced, though notably not completely eliminated, AMPH-evoked DA efflux (Chen et al, 2009). Similar results were recently observed by the Gnegy group, who found that perfusion of PKCb inhibitors into the nucleus accumbens of rats reduced AMPHevoked DA efflux by approximately 50% (Zestos et al, 2016). These authors also observed a decrease in AMPHinduced stimulation of locomotor behavior.…”
Section: +supporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with this idea, PKCb knockout mice demonstrate reduced, though notably not completely eliminated, AMPH-evoked DA efflux (Chen et al, 2009). Similar results were recently observed by the Gnegy group, who found that perfusion of PKCb inhibitors into the nucleus accumbens of rats reduced AMPHevoked DA efflux by approximately 50% (Zestos et al, 2016). These authors also observed a decrease in AMPHinduced stimulation of locomotor behavior.…”
Section: +supporting
confidence: 81%
“…These observations argue that PKCb may lie upstream in a signaling cascade connecting D2 receptor activation to ERK1/2, ultimately positively supporting DAT surface expression. In contrast to these findings, however, Zestos et al (2016) found that perfusion of PKCb inhibitors into the nucleus accumbens of rats had no effect on DA uptake in striatal synaptosomes, despite effects on AMPH-evoked DA efflux (discussed below). This lack of an effect on DA uptake in these studies may be due to the relatively short time course of PKCb inhibition (30 minutes), which may not be sufficient to observe effects on basal DA uptake like those seen in PKCb knockout mice.…”
Section: Protein Kinase C-overviewmentioning
confidence: 88%
“…This partially echoes researchers interests in compounds as a neurotransmitter but is probably also reflecting the relative ease of measuring glutamate in dialysates. Included studies describe analytical methods [4041], functional neuroanatomy [4243], basic pharmacology [4445], the neurochemistry of behaviour [464748], and the neurochemistry of several disorders (described in the introduction).…”
Section: Discussionmentioning
confidence: 99%
“…We and Giambalvo (Giambalvo, 2004; Iwata et al, 1997a) showed that amphetamine increases PKC activity in vivo and in vitro . Either inhibition (Johnson et al, 2005; Kantor and Gnegy, 1998) or deletion of PKCβ (Chen et al, 2009; Kantor and Gnegy, 1998; Zestos et al, 2016) reduces amphetamine-stimulated dopamine efflux in striatal slices from male and female rats with no change in dopamine influx. Suppression of amphetamine-stimulated dopamine efflux by PKC inhibitors was independent of extracellular Ca 2+ (as is dopamine transporter function (Raiteri et al, 1979)), the chemical class of inhibitor used, or the inhibitor binding site on PKC (catalytic vs regulatory subunits) (Kantor and Gnegy, 1998).…”
Section: Pkc Mediates Amphetamine-stimulated Dopamine Efflux and Amentioning
confidence: 99%
“…Suppression of amphetamine-stimulated dopamine efflux by PKC inhibitors was independent of extracellular Ca 2+ (as is dopamine transporter function (Raiteri et al, 1979)), the chemical class of inhibitor used, or the inhibitor binding site on PKC (catalytic vs regulatory subunits) (Kantor and Gnegy, 1998). Both a general PKC inhibitor, Ro31-8220, (Loweth et al, 2009) and enzastaurin, which is selective for PKCα and PKCβ, block amphetamine-mediated dopamine efflux in the nucleus accumbens when measured using in vivo microdialysis (Zestos et al, 2016). Molecularly, overexpression of PKCβ but not PKCα increased amphetamine-stimulated efflux from human dopamine transporter-HEK293 cells (Johnson et al, 2005).…”
Section: Pkc Mediates Amphetamine-stimulated Dopamine Efflux and Amentioning
confidence: 99%